A Study of Key Drivers of Fintech Disruption and its Impact on Traditional Banking – A Comprehensive Literature Review (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
The advent of financial technology (Fintech) has significantly reshaped the  landscape of the banking industry, introducing innovations that challenge  traditional banking models. This study aims to identify and analyse the key drivers  of fintech disruption and assess their impact on conventional banking institutions.  Through a comprehensive literature review, this research identifies critical factors  such as technological advancements, regulatory changes, customer expectations,  and competitive dynamics as primary catalysts of fintech disruption. The study  further investigates how these drivers influence the operational and strategic  responses of traditional banks, leading to changes in service delivery, customer  engagement, and business models. By examining the literature, the research  highlights the adaptive strategies employed by traditional banks to remain  competitive in a rapidly evolving financial ecosystem. The findings provide valuable  insights for policymakers, financial institutions, and fintech companies, offering a  nuanced understanding of the interplay between innovation and regulation, and  paving the way for more resilient and customer-centric banking solutions.
Keywords: Fintech; Fintech Disruption; Conventional Banking; Financial Ecosystem